VD_FINDINFO ML / 2012 / 204 vom 13. August 2012 - VD Tribunal cantonal (2012)
MAINLEVÉE DÉFINITIVE, DÉCISION DE COTISATIONS, COTISATION AVS/AI/APG | 80 LP, 54 al. 1 LPGA, 34a RAVS, 41bis al. 1 let. a RAVS